2019
DOI: 10.1039/c8nj05939j
|View full text |Cite
|
Sign up to set email alerts
|

Novel phenyl-substituted pyrazinoporphyrazine complexes of rare-earth elements: optimized synthetic protocols and physicochemical properties

Abstract: Novel synthetic protocols based on both template and direct methods were developed for phenyl-substituted pyrazinoporphyrazine complexes of rare-earth elements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 49 publications
0
4
0
1
Order By: Relevance
“…Синтез осуществлялся в соответствии с описанными протоколами для PhPorphErOAc [10], PhSubPcBBr [11] и PhNcLuPhPc [12]. Концентрации растворов, подготовленных для нанесения на подложку, составляли PhPorphErOAc (1.6 • 10 −4 М в смеси бензол : пиридин…”
Section: методика эксперимента и исследованные образцыunclassified
“…Синтез осуществлялся в соответствии с описанными протоколами для PhPorphErOAc [10], PhSubPcBBr [11] и PhNcLuPhPc [12]. Концентрации растворов, подготовленных для нанесения на подложку, составляли PhPorphErOAc (1.6 • 10 −4 М в смеси бензол : пиридин…”
Section: методика эксперимента и исследованные образцыunclassified
“…Substituted TPyzPz's are of great interest and importance because only the appropriate substituent groups can increase macrocyclic compound solubility in organic solvents or water and fine-tune the physicochemical properties necessary for a particular application (Donzello et al 2016). Lanthanide(III) mono-AzaPcs generally show good solubility and low aggregation tendency due to the steric effect of an axial ligand and the high solubility of the central lanthanide ion (Donzello et al 2022, Kosov et al 2019, Tikhomirova et al 2018. The incorporation of rare earth metal ions into the AzaPc cavity helps to improve the photophysical and photochemical properties, as well as to overcome their aggregation in solutions (Donzello et al 2022, Kosov et al 2019, Tikhomirova et al 2018) Intramolecular heavy atom effect can induce relaxation through fluorescence or singlet oxygen generation.…”
Section: Introductionmentioning
confidence: 99%
“…Lanthanide(III) mono-AzaPcs generally show good solubility and low aggregation tendency due to the steric effect of an axial ligand and the high solubility of the central lanthanide ion (Donzello et al 2022, Kosov et al 2019, Tikhomirova et al 2018. The incorporation of rare earth metal ions into the AzaPc cavity helps to improve the photophysical and photochemical properties, as well as to overcome their aggregation in solutions (Donzello et al 2022, Kosov et al 2019, Tikhomirova et al 2018) Intramolecular heavy atom effect can induce relaxation through fluorescence or singlet oxygen generation. The presence of heavy atoms in the molecule can increase the intersystem crossing of the compound.…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, Dubinina et al demonstrated that both templated and multi-step methods can be applied for efficiently synthesizing new lanthanide pyrazinoporphyrazine complexes with the assistance of both thermal and microwave irradiation techniques; the products were purified by simple precipitation from a MeOH : H 2 O (20 : 1 v/v) mixture, followed by washing with H 2 O, MeOH and acetone. 81 In 2019, by taking advantage of the larger size of Gd III compared to Fe II , Gottfried's group serendipitously obtained the template-controlled on-surface cyclopentamerization, rather than the expected formation of bis(phthalocyaninato) double deckers. 78 The resulting gadolinium(III) supernaphthalocyanine Gd-SNPc could be observed via scanning tunnelling microscopy (STM) (Fig.…”
Section: Introductionmentioning
confidence: 99%